APPLICATION DESIGN FOR LEARNING ARABIC FOR ELEMENTARY SCHOOL BASED ON MULTIMEDIA - Wisnu Uriawan; Adam Faroqi (JURNAL ISTEK, 2012)
Computer and multimedia technology is currently the center of attention, especially in gaming applications (games) with features a realistic 2D and 3D, making it very popular with the kids, especially elementary school level and equal. This happens in teaching and learning in schools, these students are only given during the learning materials through the teachers without going through an interesting instructional media such as multimedia application. Currently there are many students who have difficulty in understanding the subject matter, one of which the Arabic language lessons. Complexity of the material provided by the teacher to the students through a book is still sometimes difficult to understand, especially by students who have background can not read the Al-Quran.Learning Arabic in principle easier when accompanied with supporting media such as the application of learning the Arabic language, so students have the motivation, because the learning system is not monotone so as not to cause saturation and also help a teachers in delivering the material.Design of the application of learning the Arabic language can be used to assist students in learning the Arabic language with a written description, drawings and two language understanding (Arabic and Indonesia). Applications have been tailored to the needs for learning, and performed testing using black box method. The test results stated that all needs can be met entirely defined. Concept used in learning the Arabic language is a multimedia-based.